Misfit Sisters - Short, S. author. aut Link
XI, 196 p.
Keywords: This timely study breaks new ground in exploring how recent film and television horror texts articulate a female rite of passage, updating the cautionary concerns found in fairy tales of the past, particularly in warning against predatory men, treacherous females and unhappy family situations.